Further life expectancy in Poland and its determinants - Bojar, Wioletta (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article deals with quantifying the influence of environmental and socio-economic factors on life expectancy in Poland, that has been increasing since 1992 as a result of falling infant mortality rate, the development of civilisation and improving quality of life, among others. The process brings about changes in the number and demographic structure of the population, one outcome of which is an expanding share of elderly people. The research goal was focused on estimating econometric models that allow understanding how socio-economic factors influence life expectancy in Poland.